Predicting the future of sports organizations - Jugoslav Vojinovic; Nebojsa Maksimovic; Dragan Kokovic; Aleksandar Raic; Radenko Matic; Dragan Doder (Universidade Estadual Paulista (UNESP), 2015)
The current crisis of sport in Serbia justifies its prediction of real potential future of sport organizations. Sample of respondents (N=277) was divided in two subsamples: 113 professional persons involved in the management of sports clubs ("experimental" sample) and 164 individuals ("control" sample). The results of structural analysis showed that experimental sample based its vision on the staff as a determinant of the system, which is providing creativity as a characteristic of the organizational culture of the club. Control subsample of respondents could indicate some characteristic variables to predict the future of clubs, but can't say a clear prediction system based on a long sequence of reasoning. We can conclude that the mentioned two sub-samples are differerent in terms of the ability to orient to predict the future of their clubs on the basis of assessment of the key variables that shape the future scenarios.